The Effect of Financial Literacy, Social Media, and Social Environment towards The Consumptive Behavior of Students at SMA Negeri Kabupaten Jepara - Miftahul Jannah, Arifa; Murwatiningsih, Murwatiningsih; Oktarina, Nina (Journal of Economic Education, 2021)
Consumptive behaviour is a behaviour of consuming products excessively. The aim of this study is to find out the effects of financial literacy, social media, and social environment towards the consumptive behaviour of the students at SMA Negeri Kabupaten Jepara. It is a quantitative research study. The population used was all the eleventh grade students of elective social sciences at SMA Negeri Kabupaten Jepara which amounted to 1315 students, with 307 students as the sample of study. The researcher used questionnaire as the data collection technique. This study used a descriptive percentage and multiple linear regression analysis as the method of analysis. Results of the study showed that financial literacy has a significant negative effect on consumptive behaviour by 20.16%, social media has a significant positive effect on consumptive behaviour by 43.16%, and the social environment has a significant negative effect on consumptive behaviour by 34.45%.